2020
DOI: 10.1186/s12866-020-01953-x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Escherichia coli Nissle 1917-derived outer membrane vesicles enhance immunomodulation and antimicrobial activity in RAW264.7 macrophages

Abstract: Background: Probiotic Escherichia coli Nissle 1917 (EcN) has been widely studied for the treatment of intestinal inflammatory diseases and infectious diarrhea, but the mechanisms by which they communicate with the host are not well-known. Outer membrane vesicles (OMVs) are produced by Gram-negative bacteria and deliver microbial molecules to distant target cells in the host, which play a very important role in mediating bacteria-host communication. Here, we aimed to investigate whether EcN-derived OMVs (EcN_OM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…Most of the studies focused on OMV-host cell interaction have demonstrated the internalization of the vesicles into epithelial cells (Kunsmann et al, 2015;Mondal et al, 2016;Bielaszewska et al, 2017;O'Donoghue et al, 2017;Turner et al, 2018). Only a few studies have provided direct evidence for OMV uptake into macrophages (Pollak et al, 2012;Vanaja et al, 2016;Hu et al, 2020). This might mainly be due to the fact that, as professional phagocytes, macrophages are naturally programmed to engulf and eliminate any foreign particles, and therefore the internalization of OMV is highly assumed.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies focused on OMV-host cell interaction have demonstrated the internalization of the vesicles into epithelial cells (Kunsmann et al, 2015;Mondal et al, 2016;Bielaszewska et al, 2017;O'Donoghue et al, 2017;Turner et al, 2018). Only a few studies have provided direct evidence for OMV uptake into macrophages (Pollak et al, 2012;Vanaja et al, 2016;Hu et al, 2020). This might mainly be due to the fact that, as professional phagocytes, macrophages are naturally programmed to engulf and eliminate any foreign particles, and therefore the internalization of OMV is highly assumed.…”
Section: Discussionmentioning
confidence: 99%
“…8 a&b and Fig. 9) [77,78] . Similar findings were reported when the response of macrophages towards OMVs derived from…”
Section: Differentiation Of Macrophage Raw 2647 Cellsmentioning
confidence: 93%
“…This APEC isolate was grown in Luria–Bertani (LB) broth at 37 °C. Native OMVs were isolated and purified from bacterial culture supernatant by a series of centrifugal processes, as described in our previous studies [ 36 , 37 ]. Briefly, the bacteria-free supernatant was collected from the culture medium in the logarithmic phase by centrifugation (12,000× g , 15 min, 4 °C), and filtered through a 0.45-μm membrane (Merck Millipore, Tullagreen, Carrigtwohill, Ireland) followed by ultracentrifugation (150,000× g , 2 h, 4 °C).…”
Section: Methodsmentioning
confidence: 99%